If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 175m + -125m + 38000 = 40600 + -150m Reorder the terms: 38000 + 175m + -125m = 40600 + -150m Combine like terms: 175m + -125m = 50m 38000 + 50m = 40600 + -150m Solving 38000 + 50m = 40600 + -150m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '150m' to each side of the equation. 38000 + 50m + 150m = 40600 + -150m + 150m Combine like terms: 50m + 150m = 200m 38000 + 200m = 40600 + -150m + 150m Combine like terms: -150m + 150m = 0 38000 + 200m = 40600 + 0 38000 + 200m = 40600 Add '-38000' to each side of the equation. 38000 + -38000 + 200m = 40600 + -38000 Combine like terms: 38000 + -38000 = 0 0 + 200m = 40600 + -38000 200m = 40600 + -38000 Combine like terms: 40600 + -38000 = 2600 200m = 2600 Divide each side by '200'. m = 13 Simplifying m = 13
| 30-15b=105 | | 14+25x=35+18x | | 4x^2-36=4(x^2-36) | | (4x-3)(3x-4)=(2x-5)(6x-4) | | 2(5(2)-3)=1(2)+12 | | 8r-11-12r=4+-3r-16 | | 6x-(4-6x)=1.5(8x+12) | | 2x^2-9x^2+7=0 | | 39-8n=-8n(3+4n)+3n | | 6y^4-12xy^5= | | 9(2-a)+4a=3a | | 9x^2-18x-34=6 | | f(x)=((x+4)(x+4))-5(x+4)+9 | | 2(4y+5)+3(4y+1)= | | 7x+4+9x+8=92 | | f(x)=((x+4)(x+4))2-5(x+4)+9 | | 4y+3(y-6)+2=8 | | -3(6-10n)=10(2n-6) | | 28-5x=10+4x | | 2c+4-3x=-9+x+5 | | 9(6x-14)=3(3x+4) | | Nt+6-xt=s | | (2x-25)=180 | | 0=32+32x-16x^2 | | -5+3m+30=11m-33-8m | | 7(2+y)+5(-2-4y)= | | 8K-11+2K+1=8 | | P=2(1+1w) | | 3(6x-14)=2(7x+4) | | 57=7f | | 13k+7=7+12k | | 16-12y=4y |